Brpf1 Haploinsufficiency Impairs Dendritic Arborization and Spine Formation, Leading to Cognitive Deficits - Su, Yan; Liu, Junhua; Yu, Baocong; Ba, Ru; Zhao, Chunjie (Frontiers in Cellular Neuroscience, 2019)
Haploinsufficiency of the bromodomain and PHD finger-containing protein 1 (BRPF1) gene causes intellectual disability (ID), which is characterized by impaired intellectual and cognitive function; however, the neurological basis for ID and the neurological function of BRPF1 dosage in the brain remain unclear. Here, by crossing Emx1-cre mice with Brpf1fl/fl mice, we generated Brpf1 heterozygous mice to model BRPF1-related ID. Brpf1 heterozygotes showed reduced dendritic complexity in both hippocampal granule cells and cortical pyramidal neurons, accompanied by reduced spine density and altered spine and synapse morphology. An in vitro study of Brpf1 haploinsufficiency also demonstrated decreased frequency and amplitude of miniature EPSCs that may subsequently contribute to abnormal behaviors, including decreased anxiety levels and defective learning and memory. Our results demonstrate a critical role for Brpf1 dosage in neuron dendrite arborization, spine morphogenesis and behavior and provide insight into the pathogenesis of BRPF1-related ID.